A Case Report of Laparotomic Myomectomy After The Use of Gnrh Analogue in A Brazilian Woman - Sena-Martins, M; Tadini, V; Yamamoto, S T; Mariani Neto, C; Kuroda, C M; Santos, D F; Moreira, J M S; Carnauba, L A B; Sousa, M C; Novaczyk, M B; et al. (British Journal of Healthcare and Medical Research, 2023)
Uterine leiomyoma is the most common genital benign tumor in the female population. It is estimated that about 20 to 40% of women will have leiomyoma during their reproductive stage. IBGE (Brazilian Institute of Geography and Statistics) estimated the Brazilian population to be over 200 million Brazilians, of which half are women and approximately 50% are of reproductive age; hence, by calculating the prevalence of leiomyomatosis, there would be just over 6 million women with symptomatic fibroids in Brazil that require clinical or surgical treatment.[1-3-4] Due to its presence during the reproductive period, it can be caused by infertility or recurrent spontaneous pregnancy loss. Hence, myomectomy can be necessary when the fibroid itself causes distortion of the endometrial cavity, or competes with the embryo for the same place, or when conservative treatment was ineffective. This report describes a case of myomectomy which was performed after treatment with goserelin acetate with considerable reduction of fibroids volume, probably facilitating surgical approach, decreasing the blood loss and the risk of hysterectomy conversion. In addition, other GnRH analogue benefits before surgery such as doctor’s impression of decrease in size and better mobility of the tumor and patients feeling of decrease of the abdominal volume and the bleeding. This subjective approach can optimize the timing of surgery and establish the number of injections.